Web-Based Micro Small and Medium Enterprises Product Brand Development - Trustorini Handayani; I Widianingsih; S Julianti; D N Pebriani (Universitas Komputer Indonesia, 2021)
This research aims to determine the development of Industrial Revolution 4.0 technology in the Micro, Small, and Medium Enterprises (MSMEs) sector, to improve the standard of quality business product brands by creating a web-based information system. To support this research, we used qualitative descriptive research methods to describe existing phenomena, both natural and human engineering, that pay more attention to the characteristics, quality, and interrelationships between activities. The results show that product brand development for web-based small and medium enterprises is compelling so that it will be able to compete with other business product brands globally. This is due to a web-based information system created to introduce various products, the owners of MSMEs products. The information system was designed to input the MSME owners' data, starting from product brands, catalogs, and services. Therefore, the information system can help marketing and improve the owners' ability in the product brand development that can be used to compete in the global market. That way, the society can access various information about superior products from the MSME owners who have a product quality is no less good than other excellent products.